2022
DOI: 10.1088/1674-1056/ac1f08
|View full text |Cite
|
Sign up to set email alerts
|

Residual symmetries, consistent-Riccati-expansion integrability, and interaction solutions of a new (3+1)-dimensional generalized Kadomtsev-Petviashvili equation

Abstract: With the aid of the Painlevé analysis, we obtain residual symmetries for a new (3+1)-dimensional generalized Kadomtsev–Petviashvili (gKP) equation. The residual symmetry is localized and the finite transformation is proposed by introducing suitable auxiliary variables. In addition, the interaction solutions of the (3+1)-dimensional gKP equation are constructed via the consistent Riccati expansion method. Particularly, some analytical soliton-cnoidal interaction solutions are discussed in graphical way.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 60 publications
0
4
0
Order By: Relevance
“…The Painlevé analysis method is an effective way of judging the integrability of nonlinear differential equations and finding exact solutions. [29,30] We now perform the Painlevé analysis on Eq. ( 4) to find integrability conditions.…”
Section: Introductionmentioning
confidence: 99%
“…The Painlevé analysis method is an effective way of judging the integrability of nonlinear differential equations and finding exact solutions. [29,30] We now perform the Painlevé analysis on Eq. ( 4) to find integrability conditions.…”
Section: Introductionmentioning
confidence: 99%
“…The symmetry method is an efficient and universal method for constructing Bäcklund transformations and analytical solutions of nonlinear systems [1][2][3][4][5][6][7][8][9][10]. At the same time, the analytical solutions can describe some nonlinear phenomena and reveal some deep-seated internal relations in nonlinear systems [11][12][13][14][15][16][17][18].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, Lou discovered that, starting from the non-local symmetries of non-linear equations, the interactions, such as the soliton-Painlevé wave, soliton-cnoidal periodic wave, soliton-KdV wave, etc., can be established [1][2][3][4][5][6]. Moreover, recent researches have also shown that the interaction solutions between solitons and other non-linear excitations can also be obtained by the consistent tanh expansion (CTE) method, which is evolved from the classical tanh function expansion method [7][8][9].…”
Section: Introductionmentioning
confidence: 99%